Acute psilocybin increased cortical activities in rats - Liu, Junhong; Wang, Yuanyuan; Xia, Ke; Wu, Jinfeng; Zheng, Danhao; Cai, Aoling; Yan, Haitao; Su, Ruibin (Frontiers in Neuroscience, 2023)
Psilocybin, a naturally occurring hallucinogenic component of magic mushrooms, has significant psychoactive effects in both humans and rodents. But the underlying mechanisms are not fully understood. Blood-oxygenation level-dependent (BOLD) functional magnetic resonance imaging (fMRI) is a useful tool in many preclinical and clinical trials to investigate psilocybin-induced changes of brain activity and functional connectivity (FC) due to its noninvasive nature and widespread availability. However, fMRI effects of psilocybin on rats have not been carefully investigated. This study aimed to explore how psilocybin affects resting-state brain activity and FC, through a combination of BOLD fMRI and immunofluorescence (IF) of EGR1, an immediate early gene (IEG) closely related to depressive symptoms. Ten minutes after psilocybin hydrochloride injection (2.0 mg/kg, i.p.), positive brain activities were observed in the frontal, temporal, and parietal cortex (including the cingulate cortex and retrosplenial cortex), hippocampus, and striatum. And a region-of-interest (ROI) -wise FC analysis matrix suggested increased interconnectivity of several regions, such as the cingulate cortex, dorsal striatum, prelimbic, and limbic regions. Further seed-based analyses revealed increased FC of cingulate cortex within the cortical and striatal areas. Consistently, acute psilocybin increased the EGR1 level throughout the brain, indicating a consistent activation thought the cortical and striatal areas. In conclusion, the psilocybin-induced hyperactive state of rats is congruent to that of humans, and may be responsible for its pharmacological effects.